Perinatal Mortality among All Deliveries in a Tertiary Care Center: A Descriptive Cross-sectional Study - Saraswoti Kumari Gautam Bhattarai (Nepal Medical Association, 2021)
Introduction: Perinatal mortality comprises the number of stillbirths and death of newborns within seven days of life which is the main contributor to infant and maternal mortality. The aim of this study was to find out the prevalence of perinatal mortality among all the deliveries in a tertiary care center of a remote part of Nepal.